Pengaruh Intensitas Penggunaan Media Sosial terhadap Prestasi Belajar Siswa Kelas X di SMA - Ressa Kahayanti; O Offeny; Ahmad Saefulloh (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2021)
This study aims to determine the effect of the intensity of the use of social media on the learning achievement of class X students at SMA Muhammadiyah 1 Palangka Raya. This type of research is a quantitative study with a correlational method, the population includes all class X students of SMA Muhammmadiyah 1 Palangka Raya, totaling 145 students. The sample used was 60 students, the sampling technique in this research was probability sampling, namely simple random sampling where the sample consisted of several classes. the data collection method was done by using a questionnaire and documentation. From the trial of the intensity of the use of social media, 34 of the 40 instruments can be valid. Reliability test results with alpha cronbach intensity of use of social media obtained rxy 0.932> r table 0.330 and for student achievement obtained rxy 0.943> r table 0.330. The results of the study are: 1. The intensity of the use of social media by class X students at SMA Muhammadiyah 1 Palangka Raya is being shown by the mean (average) value of 92.82, the median value (middle value) 74.78, the mode value (the value that is appears frequently) 78.78, standard deviation 5.18. The low category was 18 students or 30%, the medium category was 16 students or 27%, and the high category was 26 students or 43%. 2. The learning achievement of class X students at SMA Muhammadiyah 1 Palangka Raya is being shown by the mean (average) 82.75, the median value (middle value) 82.90, the mode score (the valuethat often appears) 84.95, standard deviation of 2.51. It was included in the low category as many as 7 students or 12%, the medium category was 53 students or 88%, and the high category was 0 students or 0%. 3. There is an influence on the intensity of the use of social media on the learning achievement of class X students at SMA Muhammadiyah 1 Palangka Raya. With a correlation coefficient of 0.211, this shows the effect of the intensity of the use of social media on the learning achievement of class X students at SMA Muhammadiyah 1 Palangka Raya is low.